2009
DOI: 10.1371/journal.pgen.1000527
|View full text |Cite|
|
Sign up to set email alerts
|

A Network of Conserved Damage Survival Pathways Revealed by a Genomic RNAi Screen

Abstract: Damage initiates a pleiotropic cellular response aimed at cellular survival when appropriate. To identify genes required for damage survival, we used a cell-based RNAi screen against the Drosophila genome and the alkylating agent methyl methanesulphonate (MMS). Similar studies performed in other model organisms report that damage response may involve pleiotropic cellular processes other than the central DNA repair components, yet an intuitive systems level view of the cellular components required for damage su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(75 citation statements)
references
References 51 publications
(88 reference statements)
2
73
0
Order By: Relevance
“…Some studies have incorporated RNAi knockdown of DNA repair genes in vivo (e.g., Marek and Bale 2006), and in cells (e.g., Chiolo et al 2011). Ravi et al (2009) conducted an RNAi screen in Kc cells to identify genes required for resistance to MMS. Based on the 307 genes identified, and the 13 different pathways in which they function, these authors constructed an "MMS survival network.…”
Section: Other Assaysmentioning
confidence: 99%
“…Some studies have incorporated RNAi knockdown of DNA repair genes in vivo (e.g., Marek and Bale 2006), and in cells (e.g., Chiolo et al 2011). Ravi et al (2009) conducted an RNAi screen in Kc cells to identify genes required for resistance to MMS. Based on the 307 genes identified, and the 13 different pathways in which they function, these authors constructed an "MMS survival network.…”
Section: Other Assaysmentioning
confidence: 99%
“…In particular, we looked for polymorphisms likely to affect the function of genes that could affect mutation rates. To do this, we examined mutations in genes identified as being important for DNA damage repair (Ravi et al 2009), particularly those mutations resulting in premature termination codons, frameshifts, and deletions of large portions of coding sequence. While we found many genes having different nonsynonymous alleles in the two inbred lines, we did not find any inactivating mutations in genes known to be involved in processes related to G:C/A:T transitions.…”
Section: Genetic Variation In the Mutation Ratementioning
confidence: 99%
“…We performed a meta-analysis comparing hits between the present study and several other cell-growth-related Drosophila RNAi screens (Kiger et al 2003;Bettencourt-Dias et al 2004;Boutros et al 2004;Bjorklund et al 2006;Friedman and Perrimon 2006;Goshima et al 2007;Sepp et al 2008;Mummery-Widmer et al 2009;Ravi et al 2009;Sims et al 2009;Dekanty et al 2010;Kockel et al 2010). We also examined prior Drosophila genome-scale RNAi screens whose measured phenotypes were not explicitly growthrelated but whose hits included one or more canonical TORC1 pathway members (Agaisse et al 2005;Guo et al 2008;Zhou et al 2008;Zhang et al 2010).…”
Section: Meta-analysis Of S6 and S6k Regulatorsmentioning
confidence: 99%
“…A screen for regulators of cell survival following DNA damage by methane methylsulfonate (MMS) demonstrated that knockdown of Tor, raptor, S6k, or Pk61C/PDK1 promoted cell death in response to MMS, while knockdown of gig/TSC2 promoted survival (Ravi et al 2009). However, none of the canonical TORC1 pathway genes scored as hits in a prior Drosophila RNAi screen for regulators of cell count or viability under normal growth conditions (Boutros et al 2004).…”
Section: Genome-scale Rnai Identifies Torc1-s6k Regulatorsmentioning
confidence: 99%